2017
DOI: 10.1177/1753425917707025
|View full text |Cite
|
Sign up to set email alerts
|

CD14 gene silencing alters the microRNA expression profile of RAW264.7 cells stimulated by Brucella melitensis infection

Abstract: Innate recognition of Brucella spp. is a key step in the activation of inflammation. CD14 binds PAMPs and is involved in LPS-induced pro-inflammatory cytokine release. Previously we showed that knock down of CD14 in RAW264.7 macrophages disrupted Brucella-host interactions. However, its effect on the macrophage microRNA (miRNA) expression profile, especially after stimulation by Brucella infection, is still unclear. To identify miRNAs involved in the macrophage response to Brucella infection, we performed miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…However, both the p-Akt/p-Erk pathways were soon downregulated, which was associated with rapid degradation of TrkA in response to NGF stimulation and the overexpression of Cblb and Cbl genes. Similar to Takahashi's results [27][28][29][30], our co-IP data showed that TrkA ubiquitination and degradation were statistically affected by Cbl, but the domain of TrkA required for ubiquitination by Cbl remains unclear. The mechanisms of the TrkA-Cblb interaction may involve the TKB domain (an SH2like domain) promoting the binding of phosphorylated tyrosine on activated TrkA and Src homology 2 adapter Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, both the p-Akt/p-Erk pathways were soon downregulated, which was associated with rapid degradation of TrkA in response to NGF stimulation and the overexpression of Cblb and Cbl genes. Similar to Takahashi's results [27][28][29][30], our co-IP data showed that TrkA ubiquitination and degradation were statistically affected by Cbl, but the domain of TrkA required for ubiquitination by Cbl remains unclear. The mechanisms of the TrkA-Cblb interaction may involve the TKB domain (an SH2like domain) promoting the binding of phosphorylated tyrosine on activated TrkA and Src homology 2 adapter Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Through an in vitro study, we determined that the Cbl mRNA 3′ UTR was the target of miR-145-5p and that the Cblb mRNA 3′UTR was the target of miR-199a-3p. The predicted biding site of Cbl mRNA for miR-145-5p is first reported and proved by us; interestingly, the predicted biding site of Cblb mRNA for miR-199a-3p was previously reported but not examined in RAW264.7 cells by Rong [29].…”
Section: Discussionmentioning
confidence: 68%
“…The authors observed up-regulation of mmu-miR-199a-3p and mmu-miR-183-5p. Interestingly, among the predicted target genes of mmu-miR-199a-3p and mmu-miR-183-5p, the significantly enriched gene ontology terms were the apoptosis process, immune response, inflammatory response, innate immune response, anti-apoptosis, cytokine production, and cytokine-mediated signalling pathway [ 37 ]. In one of our previous studies, more than 2,000 miRNAs were screened in peripheral blood mononuclear cells of patients with acute or chronic brucellosis, and we determined that while the expression level of miR-1238-3p increased, miR-494, miR-6069, and miR-139-3p decreased in the chronic group compared to the acute group.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the ability of another chronic intracellular pathogen, Mycobacterium tuberculosis, to manipulate host innate responses, autophagy, and apoptosis via host miRNA has garnered much interest [43][44][45][46]. In contrast, there is much less information regarding miRNA in the context of Brucella infection [47][48][49]. Budak et al investigated the miRNA expression patterns in CD4+ and CD8+ T cells from patients, and reported discrete changes with acute vs. chronic brucellosis [50,51].…”
Section: Discussionmentioning
confidence: 99%